Research on the Construction of an Unified Model of Enterprise Blockchain Technology Adoption Behavior in the Food Supply Chain Field - Kunpeng YU; Wei LI; Xin LEI (Shipin gongye ke-ji, 2023)
The low adoption rate and lack of industry-level large-scale applications are prominent problems facing the application of blockchain technology in the food supply chain field today. By integrating existing fragmented research, this paper provides a more systematic model of enterprise blockchain technology adoption behavior, which can not only provide theoretical support for academia to explore and understand enterprise blockchain technology adoption behavior, but also provide references for enterprises to promote blockchain project implementation decisions. By reviewing and combing relevant studies both domestic and overseas, integrating the core viewpoints of behavior reasoning theory, technology-organization-environment framework, innovation diffusion, and social capital, this paper constructs an unified model of enterprise blockchain technology adoption behavior in food supply chain field, and theoretically and normatively explains the antecedent factors that affect enterprise blockchain technology adoption intention. The model shows that enterprises form technology adoption intention by reasoning and judging 23 push and constraint factors under three dimensions of technological characteristics, organizational characteristics, and environmental characteristics, which drive technology adoption behavior. Therefore, enterprises should focus on strengthening the impact of push factors and preventing the impact of constraint factors to promote the adoption and implementation of blockchain technology more effectively.